Interplay between Cellular and Molecular Inflammatory Mediators in Lung Cancer - Mario Orozco-Morales; Giovanny Soca-Chafre; Pedro Barrios-Bernal; Norma Hernández-Pedro; Oscar Arrieta (Mediators of Inflammation)
Inflammation is a component of the tumor microenvironment and represents the 7th hallmark of cancer. Chronic inflammation plays a critical role in tumorigenesis. Tumor infiltrating inflammatory cells mediate processes associated with progression, immune suppression, promotion of neoangiogenesis and lymphangiogenesis, remodeling of extracellular matrix, invasion and metastasis, and, lastly, the inhibition of vaccine-induced antitumor T cell response. Accumulating evidence indicates a critical role of myeloid cells in the pathophysiology of human cancers. In contrast to the well-characterized tumor-associated macrophages (TAMs), the significance of granulocytes in cancer has only recently begun to emerge with the characterization of tumor-associated neutrophils (TANs). Recent studies show the importance of CD47 in the interaction with macrophages inhibiting phagocytosis and promoting the migration of neutrophils, increasing inflammation which can lead to recurrence and progression in lung cancer. Currently, therapies are targeted towards blocking CD47 and enhancing macrophage-mediated phagocytosis. However, antibody-based therapies may have adverse effects that limit its use.